Actinophytocola sp. K4-08: rare actinomycete with potential biosynthetic capability - Mohd Zin, Nur Huda; Zainal Abidin, Zaima Azira; Abdul Malek, Nurfathiah; Azizan, Nur Hafizah; Darnis, Deny Susanti (2018)
Thousands of antibiotics have been found from different actinomycetes but there were less study recorded on antimicrobial activity of rare actinomycete especially Actinophytocola sp. K4-08. Studies showed that evaluation on the antimicrobial potential of members of this genus has not been attempted so far, making it a prominent source of novel bioactive compounds.Therefore, the present study was carried out to isolate and identify antimicrobial activity of rare actinomycete, Actinophytocola sp. K4-08. Actinophytocola sp. K4-08 was successfully isolated from Kuantan mangrove sediment on starch-yeast extract agar (SYE) medium. Abundant cream colored substrate mycelium was formed on SYE and no obvious diffusible pigment was produced within 21 days of incubation. Partial 16S rRNA gene sequence revealed that Actinophytocola sp. K4-08 possessed 99% similarity to Actinophytocola sediminis YIM 75636. Moreover, both PKS-I and NRPS genes, both of which usually related to secondary metabolite potential were detected in this isolate through PCR amplification. Preliminary screening using cross streak test showed that Actinophytocola sp.K4-08 displayed antibacterial activity against B. subtilis and S. aureus. Its crude ethyl acetate extracts also displayed inhibitory activity against B. subtilis, further confirming the antimicrobial properties of this isolate. Actinophytocola sp. K4-08 was cultured in SYE broth followed by centrifugation to separate the cells and the supernatant. XAD-resin was added to the supernatant of 21-days culture broth followed by extraction with acetone. Crude ethyl acetate extract from the supernatant was also prepared and cells of Actinophytocola sp. K4-08 was extracted with methanol. All extracts (supernatant and cells) produced dark orange solid and yellow coloured oil. Disc diffusion assay against B. subtilis with concentration of 20, 40, 60, 80 and 100 µg/disc was conducted to check on the antibacterial capabilities of the extracts. All extracts (solid and oil) displayed weak inhibition activity against B. subtilis with oil possessed higher inhibition activity compared to the solid. Although the extracts produced weak antibacterial activity, nevertheless, the potential of rare actinomycete Actinophytocola sp. K4-08 indicated potential as bioactive compound producer that is worth exploring. Further investigation is needed in an attempt to isolate, purify and elucidate potential bioactive compounds produced by Actinophytocola sp. K4-08.